Sustainable Operations Management: Advances in Strategy and Methodology - Chiarini, Andrea (Springer, 2015)
This book presents innovative research on various aspects of sustainability in the field of operations management and illustrates the potential of sustainability thinking and practice to improve operations performance and thereby meet customer needs. Particular attention is devoted to corporate social responsibility and marketing strategy, knowledge management for sustainability, the role of culture in a sustainable built environment, sustainable manufacturing through the application of lean and green concepts, advancing sustainability through ISO standards, and the sustainable supply chain.